Exploring reading self-efficacy among EFL learners from different academic disciplines - Sukserm, Patsawut (Studies in English Language and Education, 2025)
Reading self-efficacy plays a crucial role in the academic success of EFL learners, yet the extent to which it varies across academic disciplines remains underexplored. This study aims to (1) examine the level of reading self-efficacy among EFL learners from business, social sciences, and sciences; (2) investigate the relationship between different components of reading self-efficacy; and (3) compare self-efficacy levels across these academic disciplines. A total of 217 university-level EFL students in Thailand participated in the study. A 25-item reading self-efficacy questionnaire with strong reliability (Cronbachs alpha = 0.915) was employed. Data were analyzed using descriptive statistics, Pearson correlations, and ANOVA. The results reveal significant positive correlations between assessment of content (AOC) and summary of content (SOC) (r = 0.522, p 0.001), and between opinion on content (OOC) and SOC (r = 0.387, p 0.001). ANOVA results indicate significant differences in recognition of content elements (ROE) across disciplines, with business students scoring higher than science students (p = 0.015). Business students also demonstrated significantly higher self-efficacy in OOC compared to social science and science students (p = 0.001). These findings suggest that reading self-efficacy is influenced by students academic disciplines, supporting the view that self-efficacy is task-specific and context-dependent. Therefore, EFL instructors should implement tailored instructional approaches that address discipline-specific reading challenges to enhance students reading confidence and academic performance.